Application of the suggestopedia method for the improvement of oral communication in the english language among the students of the general basic education of the high School Nueve de Octubre - Buñay Betun, Jhonatan Armando; Santana Gómez, John Henry (Machala: Universidad Técnica de Machala, 2024)
The main objective of the present work was to implement a class system using the Suggestopedia method to improve secondary school students' oral communication in English. The specific objectives were to identify the methods and activities used in English language teaching, to show the current level of development of oral skills, to design a class system with Suggestopedia activities and to analyse the results after implementing this method. The research was carried out using a quantitative empirical-analytical approach to identify the possible causes of students' poor oral communication. Techniques such as non-participant observation, measurement, pedagogical tests and questionnaires were used to collect data. The results of the post-test showed significant improvements compared to the pre-test in all the indicators assessed. This suggests that the implementation of the Suggestopedia activities had a positive effect on the students' oral communication in English. Therefore, the null hypothesis was accepted, confirming that the use of Suggestopedia as a method improves the oral communication in English of the first year at Nueve de Octubre High School, in room D. These results support the idea that this method, by creating a relaxed and motivating learning environment, facilitates the acquisition and use of the language in a natural and fluent way. Therefore, it is recommended that this method be included in the teaching unit at all levels of primary and secondary education.
El presente trabajo tuvo como objetivo principal fue implementar un sistema de clase mediante el uso del método Sugestopedia para mejorar la comunicación oral en inglés de los estudiantes de secundaria. Los objetivos específicos incluyeron identificar los métodos y actividades utilizados en la enseñanza del inglés, demostrar el nivel actual de desarrollo de las competencias orales, diseñar un sistema de clases con actividades de Sugestopedia y analizar los resultados tras aplicar este método. La investigación se llevó a cabo desde un enfoque cuantitativo empírico-analítico, que permitió identificar las posibles causas de la baja comunicación oral de los estudiantes. Se utilizaron técnicas como la observación no participante, la medición, pruebas pedagógicas y cuestionarios para recopilar datos. Los resultados del post-test mostraron mejoras significativas en comparación con los del pre-test en todos los indicadores evaluados. Esto sugiere que la implementación de actividades de Sugestopedia tuvo un efecto positivo en la comunicación oral en inglés de los estudiantes. En consecuencia, se aceptó la hipótesis nula, lo que confirmó que el uso de la Sugestopedia como método mejora la comunicación oral en inglés de los estudiantes de primero de BGU del Colegio de Bachillerato 9 de Octubre. Estos resultados respaldan la idea de que este método, al crear un ambiente de aprendizaje relajado y motivador, facilita la adquisición y el uso del idioma de manera natural y fluida. Por lo tanto, se recomienda la incorporación de este método en todos los niveles de educación básica y bachillerato en la unidad educativa.
Keywords: SUGGESTOPEDIA; ORAL COMMUNICATION